Whole-transcriptome analysis reveals virulence-specific pathogen−host interactions at the placenta in bovine neosporosis - Horcajo, Pilar; Coronado, Montserrat; Pastor-Fernández, Iván; Collantes-Fernández, Esther; Rico-San Román, Laura; Reyes-Palomares, Armando; Ortega-Mora, Luis-Miguel (Frontiers in Immunology, 2023)
Research on bovine neosporosis has achieved relevant milestones, but the mechanisms underlying the occurrence of foetal death or protection against foetal death remain unclear. In a recent study, placentas from heifers challenged with the high-virulence isolate Nc-Spain7 exhibited focal necrosis and inflammatory infiltrates as soon as 10 days post-infection (dpi), although parasite detection was minimal. These lesions were more frequent at 20 dpi, coinciding with higher rates of parasite detection and the occurrence of foetal death in some animals. In contrast, such lesions were not observed in placentas from animals infected with the low-virulence isolate Nc-Spain1H, where the parasite was detected only in placenta from one animal at 20 dpi. This work aimed to study which mechanisms are triggered in the placentas (caruncles and cotyledons) of these pregnant heifers at early stages of infection (10 and 20 dpi) through whole-transcriptome analysis. In caruncles, infection with the high-virulence isolate provoked a strong proinflammatory response at 10 dpi. This effect was not observed in heifers infected with the low-virulence isolate, where IL-6/JAK/STAT3 signalling and TNF-alpha signalling via NF-κB pathways were down-regulated. Interestingly, the expression of E2F target genes, related to restraining the inflammatory response, was higher in these animals. At 20 dpi, more pronounced proinflammatory gene signatures were detectable in heifers infected with the high-virulence isolate, being more intense in heifers carrying dead fetuses. However, the low-virulence isolate continued without activating the proinflammatory response. In cotyledons, the response to infection with the high-virulence isolate was similar to that observed in caruncles; however, the low-virulence isolate induced mild proinflammatory signals at 20 dpi. Finally, a deconvolutional analysis of gene signatures from both placentome tissues revealed a markedly higher fraction of activated natural killers, M1 macrophages and CD8+ T cells for the high-virulence isolate. Therefore, our transcriptomic analysis supports the hypothesis that an intense immune response probably triggered by parasite multiplication could be a key contributor to abortion. Further studies are required to determine the parasite effectors that govern the distinct interactions of high- and low-virulence isolates with the host, which could help elucidate the molecular processes underlying the pathogenesis of neosporosis in cattle.